Poor Performance on a Preoperative Cognitive Screening Test Predicts Postoperative Complications in Older Orthopedic Surgical Patients. (November 2017) - Culley, Deborah J.; Flaherty, Devon; Fahey, Margaret C.; Rudolph, James L.; Javedan, Houman; Huang, Chuan-Chin; Wright, John; Bader, Angela M.; Hyman, Bradley T.; Blacker, Deborah; Crosby, Gregory
Abstract : Background: The American College of Surgeons and the American Geriatrics Society have suggested that preoperative cognitive screening should be performed in older surgical patients. We hypothesized that unrecognized cognitive impairment in patients without a history of dementia is a risk factor for development of postoperative complications. Methods: We enrolled 211 patients 65 yr of age or older without a diagnosis of dementia who were scheduled for an elective hip or knee replacement. Patients were cognitively screened preoperatively using the Mini-Cog and demographic, medical, functional, and emotional/social data were gathered using standard instruments or review of the medical record. Outcomes included discharge to place other than home (primary outcome), delirium, in-hospital medical complications, hospital length-of-stay, 30-day emergency room visits, and mortality. Data were analyzed using univariate and multivariate analyses. Results: Fifty of 211 (24%) patients screened positive for probable cognitive impairment (Mini-Cog less than or equal to 2). On age-adjusted multivariate analysis, patients with a Mini-Cog score less than or equal to 2 were more likely to be discharged to a place other than home (67% vs . 34%; odds ratio = 3.88, 95% CI = 1.58 to 9.55), develop postoperative delirium (21% vs . 7%; odds ratio = 4.52, 95% CI = 1.30 to 15.68), and have a longer hospital length of stay (hazard ratio = 0.63, 95% CI = 0.42 to 0.95) compared to those with a Mini-Cog score greater than 2. Conclusions: Many older elective orthopedic surgical patients have probable cognitive impairment preoperatively. Such impairment is associated with development of delirium postoperatively, a longer hospital stay, and lower likelihood of going home upon hospital discharge. Abstract : In a prospective clinical investigation of patients 65 yr or older without dementia having elective hip or knee replacement, screened preoperatively with the Mini-Cog, 24% were found to have probable cognitive impairment. Patients with probable preoperative cognitive impairment, compared to those patients without, were more likely to be discharged to a place other than home, develop postoperative delirium, and have a longer hospital length of stay. Preoperative cognitive screening of older surgical patients may be valuable for risk assessment and risk stratification in older surgical patients.